Penyuluhan Kesehatan Pencegahan Demam Berdarah Dengue di SD Negeri 2 Sindangsari - Sultan Al Adami pradana; Rizky Perdana Susanto; Sukamara Aji Falah; Shofia Siti Adawiah; Sinta Siti Rahma; Tiara Cahya Rinukti; Sari Puspayanti (Kolaborasi: Jurnal Pengabdian Masyarakat, 2023)
Introduction: Dengue virus infection often occurs during the rainy season, which is caused by the bite of the Aedes Aegepti mosquito, geographical and environmental conditions are for the main supporting factors for the spread and breeding of Aedes aegepti mosquitoes which cause an increase in cases of dengue hemorrhagic fever. The prevention program seeks to reduce the breeding potential of mosquito larvae which are the cause of dengue fever cases. Objective: This Community Service Program aims to increase knowledge, self-management and the environment as an effort to prevent dengue fever from spreading in communities Two sindangsari of public elementary shcool. Method: The health education program's is using the sampling method with 30 people used as a sample that aims to increase knowledge supported by media leaflets, Power Point presentations, animation, discussions, questions and answers, and interviews, covering the preparation stage to individual evaluation. Result: The results of this health counseling activity were that 10 (33.3%) of the total participants who attended the counseling had contracted dengue fever and had been hospitalized. Conclusion: The conclusions of this activity are leaflets, presentations and animated videos as media for prevention education.